Analisis Sistem Pengelolaan Resume Medis Rawat Inap Di Rumah Sakit Umum Muhammadiyah Babat: Analysis of Inpatient Medical Resume Management System at Muhammadiyah Babat General Hospital - Firmansyah, Feberlian Randiawan (Universitas Ahmad Dahlan, 2023)
Background: A medical record is a summary of the entire treatment and care period a patient undergoes while receiving medical attention at a hospital. Incomplete medical records result in a lack of information about the patient's condition, which can adversely affect various concerned parties. The aim of this study is to analyze the inpatient medical records at Muhammadiyah General Hospital Babat by identifying the completeness of these records. Methods: The research design employed is a descriptive quantitative method. The study was conducted from February to August 2023. The population of this study comprises all inpatient medical record files from February to March 2023, totaling 487 medical record files. The sampling technique employed is total sampling. The variable of this research is the Completeness of Inpatient Medical Record Filling. Results: Based on the research findings, it can be elucidated that there are two main categories within medical records: complete and incomplete medical records. From the available data, it is revealed that the percentage of complete medical records, as indicated, is 76%. Conversely, data also reveals that 24% of the sampled medical records do not meet the expected level of completeness. This incompleteness is attributed to various indicators, including primary complaints, diagnosis, treatment/procedures, supporting examination results, encountered problems, discharge conditions, prognosis, causes of death, and proposed follow-up actions. Conclusion: To address this issue, the researchers anticipate a focus on enforcing adherence to medical record filling through continuous dissemination to healthcare personnel responsible for completing the medical records. Standard operating procedures, training, and reward-punishment mechanisms are suggested approaches.